Dampak Pertambangan Emas Tanpa Izin (Peti) Terhadap Patologi Sosial Remaja Desa Padang Jering, Sarolangun - Suhar Midi (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
This research is motivated by the phenomenon that occurs, namely the rise of cases of gold mining without a permit. This is exacerbated by the observations of researchers who found teenagers who joined illegal gold miners. The type of research used is field research, using a descriptive qualitative approach. The lack of knowledge and socialization carried out by both parents and related parties causes many teenagers who do not know how dangerous gold mining without a permit is if it continues without serious handling. This is exacerbated by the low level of education and the lack of types of work that they can do apart from mining gold without a permit. In addition, the lack of firmness in the actions taken by related parties resulted in illegal gold mining cases continuing to occur in Padang Jering Village, Batang Asai District, Sarolangun Regency. Researchers argue in this study that the impact of gold mining without a permit is divided into two, namely the creation of very promising new jobs and the destruction of the surrounding environment. This is because those who become unlicensed gold miners only think about the results of what they dig, but the huge impact of what they have done is unthinkable and if this continues it will not be possible.